2016
DOI: 10.7205/milmed-d-15-00545
|View full text |Cite
|
Sign up to set email alerts
|

Economic Value of Prosthetic Services Among Medicare Beneficiaries: A Claims-Based Retrospective Cohort Study

Abstract: Patients who received lower extremity prostheses had comparable Medicare episode payments ($6,099 per-member-per-month for study group, $6,015 per-member-per-month for comparison group) and better outcomes than patients who did not receive prostheses. Study group patients were more likely to receive extensive outpatient therapy than comparison group patients (p < 0.05). Receiving physical therapy is associated with fewer hospitalizations and emergency room visits, and less facility-based care (p < 0.05), essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 6 publications
1
43
0
Order By: Relevance
“…Ultimately, this would help establish much needed CPGs (5). All factors should be considered when determining walking capacity, as not walking following amputation could lead to physical deterioration and comorbidities and be detrimental to overall health (6,7). …”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, this would help establish much needed CPGs (5). All factors should be considered when determining walking capacity, as not walking following amputation could lead to physical deterioration and comorbidities and be detrimental to overall health (6,7). …”
Section: Introductionmentioning
confidence: 99%
“…Information on cost-effective prosthetic/orthotic interventions is needed, as this will provide an evidence base for their provision to healthcare providers and policy makers. While our search found no RCTs which examined cost-effectiveness of prosthetic provision a study recently published in a Special Issue of Military Medicine [22] analysed Medicare claims data and found that individual who received lower extremity prostheses had comparable Medicare episode payments and better outcomes than those who did not receive prostheses. Individuals who were provided with prostheses were more likely to receive extensive outpatient therapy; and receiving physical therapy was associated with fewer hospitalisations and emergency room visits, and less facility-based care.…”
Section: Resultsmentioning
confidence: 99%
“…We will argue that prosthetic care is so important for the overall health of users that it is economically beneficial for health insurances to deliver the best possible care. This has already been pointed out in some studies [8,9], but is still not widely acknowledged by insurances, in Germany also due to the short-term budget allocation scheme in the health care system [10] (p. 61). We posit that there are ways to efficiently improve prosthetic care, minimising the burden on the health care budget, in particular social aspects of acceptance are taken more systematically into account.…”
Section: Introductionmentioning
confidence: 93%
“…By doing so, probably not only quality of life may improve but also resources may be allocated more efficiently by reducing long-term negative side effects of failed prosthetic care such as a lack of acceptance of and adaptation problems with prostheses as well as by reducing costs in its research and development phase. It has already been shown, for example, that prosthetic care for high-cost knee prostheses is beneficial for the insurance budget in the long term, if compared to the use of such prostheses without care [8,9]. Biddiss et al point out that there are possibilities to reduce costs of prosthetic limbs by technical means like computer-aided design and manufacturing, and due to new market opportunities [1].…”
Section: Improvements Of Prosthetic Care From the Perspective Of Socimentioning
confidence: 99%